Screening for retinopathy of prematurity in China: a five-year cohort study in seven screening centers - Yusheng Zhong; Xiacheng Lin; Yating Yang; Liying He; Na Li; Jun Lu; Yu Zhou; Rong Zhang; Yacong Wang; Zhongyu Zhang; Mochi Yang; Hong Yin; et al. (BMC Ophthalmology)
Abstract Background To analyze the demographic characteristics of retinopathy of prematurity (ROP) in China, attempting to propose optimized screening criteria and hopefully providing valuable information for future updates to the ROP guideline. Methods A multicenter, retrospective-cohort study was conducted. The study included infants born between January 1, 2018, and July 31, 2023, who underwent ROP screening and were diagnosed with ROP at seven screening centers in China. Examinations were carried out in accordance with the ROP guidelines in 2014: infants with a gestational age (GA)<32 weeks and/or birth weight (BW)<2000 g, or infants who were suspected to be at risk of ROP. ROP treatment followed the recommendations of the Early Treatment for Retinopathy of Prematurity Cooperative Group. We utilized receiver operating characteristic (ROC) curves to determine the optimal predictive model, and conducted internal validation as well as compared the model to current standards. Results Among the 4770 infants diagnosed with ROP after fundus screening, 1330 (27.9%) infants received treatment. The mean GA at birth for all enrolled infants was 29.67 ± 2.45 weeks, with a mean BW of 1295.89 ± 403.64 g. This study proposed the optimization of guidelines to be ≤ 30 weeks of GA and ≤ 1600 g of BW, achieving a sensitivity of 99.4%, as high as the current standard, with an 18.0% reduction in screening requirements. Conclusion Considering the decrease in both GA and BW among the population requiring ROP treatment in China, it is imperative to contemplate updating the ROP screening guideline.